Environmental Mapping of Post-Starburst Galaxies - Costa, Rafaela Conz; Rembold, Sandro (Cadernos de Astronomia, 2026)
Summary of the poster presented in the third edition of the As Astrocientistas event, held between March 31st and April 4th, 2025.